Attitude and practice regarding effective blood pressure measurement among health professionals at a tertiary care hospital in Hyderabad - Pakistan - Zaman, Rabail; Anam, Sobia; Muhammad Muneeb,; Ashraff, Sabry (International Journal of Endorsing Health Science Research, 2019)
Background: Blood pressure (BP) measurement is one of the basic indicator used for the diagnosis, treatment and research investigations of Hypertension. The accuracy of the measurements have the potential to influence the decision making and therefore is a prerequisite, regardless of which technique is used. Still, too often the accuracy of measurement is taken for granted in general practice. This study aims to gauge the attitude and practice of health professionals regarding effective BP measurement at a tertiary care hospital. Methodology: This cross-sectional study comprised of 50 healthcare professionals, chosen via purposive sampling from Liaquat University Hospital, a tertiary care hospital at Jamshoro, Hyderabad during November, 2015 to January, 2016. A self-administered structured qualitative and quantitative questionnaire was used to evaluate the attitude and practice of effective BP measurement. The data was analyzed through SPSS version 19 and Microsoft Excel. Results: According to the study results, 88% of the participants had clinical experience of up to 5 years. Around 56% of the respondents rated their BP measurement skills as very good, 38% as good while 6% as acceptable. It was found that 46% of the respondents use to measure BP only once whereas 54% do it twice to get a mean value. For the location of measuring the BP, 60% responded to use only one arm while, 40% reported to measure it from both arms. Furthermore, many of the respondents reported for never attending any Continuous Medical Education (CME) regarding BP measurement along with the 48%, who declared that they had never updated their knowledge regarding BP measurement guidelines. Conclusion: It is evident from the survey that selected set of healthcare professionals had lesser focus toward accurate methods of BP measurement as well as low interest in updating their knowledge regarding the standard protocols. It is concluded that up gradation of knowledge and awareness reading standard and current practices must be taught regularly and must be mandatory to follow for all healthcare providers.